2018
DOI: 10.1177/0960327118816137
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C ameliorates the adverse effects of dexamethasone on sperm motility, testosterone level, and spermatogenesis indexes in mice

Abstract: Background: Dexamethasone (DEX) is a common medicine that is capable of causing malformation in the male reproductive system. The aim of this study was to investigate the effect of vitamin C (Vit-C) on spermatogenesis indexes and daily sperm production (DSP) in adult mice treated with DEX. Methods: Male Naval Medical Research Institute (NMRI) mice were divided into four groups: Control, DEX (7 mg/kg/day), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 27 publications
6
34
2
Order By: Relevance
“…Moreover, the testicular seminiferous tubules of the low and high dose treated quails did not show all stages of spermatogenesis and only show the stages till primary spermatocyte or secondary spermatocyte or till spermatid with wide lumen filled with tissue debris with morphologically abnormal cells. Similar result was reported by Sadeghzadeh et al (2019) who stated that DEX treatment has a strong effect on the testis as it cause atrophy of the seminiferous tubules germinative epithelium. The present findings are in line with Hanafy et al (2018) where low stressed male quail showed higher testes weights and less testicular injury than males selected for overstated stress response.…”
Section: Testissupporting
confidence: 87%
“…Moreover, the testicular seminiferous tubules of the low and high dose treated quails did not show all stages of spermatogenesis and only show the stages till primary spermatocyte or secondary spermatocyte or till spermatid with wide lumen filled with tissue debris with morphologically abnormal cells. Similar result was reported by Sadeghzadeh et al (2019) who stated that DEX treatment has a strong effect on the testis as it cause atrophy of the seminiferous tubules germinative epithelium. The present findings are in line with Hanafy et al (2018) where low stressed male quail showed higher testes weights and less testicular injury than males selected for overstated stress response.…”
Section: Testissupporting
confidence: 87%
“…Dexamethasone inhibits serum luteinising hormone (LH) (Ristić et al, 2016) and testosterone (Sadeghzadeh, Mehranjani, & Mahmoodi, 2019), which affect the testicular endocrine function; therefore, it affects sperm transportation, sperm metabolism and sperm maturation in the epididymis (Tsantarliotou et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that both drugs could reduce testosterone levels in rodents or isolated cells 28,55 as this anti‐androgenic effect was reported for other COX‐inhibitors, such as paracetamol, 56 indomethacin, 57 or ibuprofen 58 . The reduction of testosterone levels by dipyrone or ASA could also induce an impairment of spermatogenesis, with a decrease in daily sperm production; this is also reported for other agents with similar ability to interfere with androgen synthesis, such as fluoxetine, 33 dexamethasone, 59 bisphenol‐A, 60 amongst others 11,61 …”
Section: Discussionmentioning
confidence: 66%